Pengaruh Konseling Behavioristik Terhadap Sikap Keuletan pada Siswa Kelas VIII SMP Negeri 3 Batukliang Utara - Gunawan, I Made; Endriani, Ani; Malina, Ria (Universitas Pendidikan Mandalika (UNDIKMA), 2019)
This study aimed to study the effect of Behavioristic Counseling on students’ tenacity attitudes of class VIII at SMPN 3 Batukliang Utara. This research used the experimental method. Samples of the study were 6 students who had a low tenacity attitude. Data collection technique used was questionnaire, observation, interview, and documentation. The data analysis technique used the t-test formula. The results of the study showed that the value of t count was 2.890 and the value of t table was 2.015 at the level of significance 5% with N = 5, in which the value of t count was greater than the value of the t table (2.890> 2.015). So, it can be concluded that there is an effect of Behavioristic Counseling on students’ tenacity attitudes of class VIII at SMPN 3 Batukliang Utara